Efficacy of Herbicides on the Yield of Lentil (Lens culinaris Medik.) (The Agriculturists, 2013)
A field experiment was conducted at Bangladesh Agricultural Research Institute, Gazipur during rabi (winter) season of 2008-09 to observe the efficacy of two herbicides on the yield of lentil (BARI masur-5). Paraxon, Whipsuper, Ronstar and Topstar were the herbicidal treatments applied after sowing of seeds and two leaf stage of weeds according to their mode of action. Dry weight of weed samples were recorded at 25 DAS and 40 DAS. The dry weight of weeds was found to be maximum in unweeded control. The highest yield of lentil 1086.6 kg ha-1 was observed when Whipsuper was applied while the control treatment showed the lowest yield (626.7 kg ha-1). A negative correlation existed between the weed dry matter weights and seed yield of lentil. DOI: http://dx.doi.org/10.3329/agric.v11i1.15248 The Agriculturists 2013; 11(1) 89-94